International Network of Twin Registries (INTR): Building a Platform for International Collaboration. (28th November 2014) - Buchwald, Dedra; Kaprio, Jaakko; Hopper, John L.; Sung, Joohon; Goldberg, Jack; Fortier, Isabel; Busjhan, Andreas; Sumathipala, Athula; Cozen, Wendy; Mack, Thomas; Craig, Jeffrey M.; Harris, Jennifer R.
<x content-type="archive" xml:space="preserve">Abstract</x> The International Network of Twin Registries (INTR) aims to foster scientific collaboration and promote twin research on a global scale by working to expand the resources of twin registries around the world and make them available to researchers who adhere to established guidelines for international collaboration. Our vision is to create an unprecedented scientific network of twin registries that will advance knowledge in ways that are impossible for individual registries, and includes the harmonization of data. INTR will also promote a broad range of activities, including the development of a website, formulation of data harmonization protocols, creation of a library of software tools for twin studies, design of a search engine to identify research partners, establishment of searchable inventories of data and biospecimens, development of templates for informed consent and data sharing, organization of symposia at International Society of Twin Studies conferences, support for scholar exchanges, and writing grant proposals.